Opinion leadership in India - "Sen, Lalit K." (Hyderabad, 1969)
The research reported in this monograph is part of a larger study entitled "Diffusion of Innovations in Rural Societies" directed by Everett M. Rogers of the department of Communication, Michigan State University, under contract with the United States Agency for International Development, and has included three countries : Brazil, Nigeria and India.
Keywords: Sociology